2016
DOI: 10.1002/prep.201600115
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Behavior of Polytetrafluoroethylene/Al Granular Composites Subjected to Planar Shock Wave

Abstract: The shock‐compression responses of PTFE (polytetrafluoroethylene)/Al granular composites subjected to planar shock waves of various pressures are investigated. A 57‐mm diameter single‐stage gas‐gun and 50‐mm diameter plane‐wave lenses are employed to perform planar shock wave experiments. High frequency manganin piezoresistance stress gauges are used to monitor the stress (regarded as pressure in consideration of the high pressure state) at four Lagrangian positions of the PTFE/Al granular composites specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The former includes drop weight tests and SHPB tests, and the latter includes plate impact and blast loads. Guo et.al [7] observed that reactions of Al-PTFE occurred in the rising period of the input shock wave generated by plane-wave lense, which means the reaction was directly triggered by the intense shock wave within 2.5-5 ms. According to their ex-perimental results, the amplitude of the shock wave required to trigger this kind of reaction is at least 8-10 GPa, which is very difficult to be achieved in drop weight tests or in SHPB tests.…”
Section: Fracture Induced Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former includes drop weight tests and SHPB tests, and the latter includes plate impact and blast loads. Guo et.al [7] observed that reactions of Al-PTFE occurred in the rising period of the input shock wave generated by plane-wave lense, which means the reaction was directly triggered by the intense shock wave within 2.5-5 ms. According to their ex-perimental results, the amplitude of the shock wave required to trigger this kind of reaction is at least 8-10 GPa, which is very difficult to be achieved in drop weight tests or in SHPB tests.…”
Section: Fracture Induced Reactionmentioning
confidence: 99%
“…They observed a significant decrease of the initiation threshold stress from 2.6 GPa to 0.7 GPa when reducing the Al particle size from 120 mm to 9 mm. Guo et.al [7] performed planar shock wave experiments on Al-PTFE by gas-gun and plane-wave lenses. They found that reactions of Al-PTFE occurred in the rising period of the input shock wave, which confirmed the SIR process of Al-PTFE under high-speed impact.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when designing the prefabricated fragment structure to improve the power and efficiency of the high explosive charge, the prefabricated fragment can be prepared with reactive materials, which can greatly improve the damage efficiency of the high explosive charge [9, 10]. Compared with traditional inert fragments, reactive fragments not only penetrate and destroy the target by relying on their kinetic energy, but also produce a chemical reaction and release energy under the strong impact, to enhance the damage ability to the target [11, 12]. If the projectile casing is replaced with reactive material, compared with the traditional inert casing, the fragments produced by the reactive metal casing can not only produce kinetic energy damage but also couple this kinetic energy with the secondary energy release generated by the rapid chemical reaction during fragment impact, resulting in an additional strengthening effect on the air shock wave [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its excellent properties and good application prospects, MESMs have been widely concerned and vigorously studied all over the world [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Wang et al [ 6 ] have done a lot of theoretical and experimental research on the impact-induced reaction characteristics of fluoropolymer-based energetic reaction fragments.…”
Section: Introductionmentioning
confidence: 99%